NAD+ Metabolism and Immune Regulation: New Approaches to Inflammatory Bowel Disease Therapies - Chaoyue Chen; Wei Yan; Meihui Tao; Yu Fu (MDPI AG, 2023)
Inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), is a multifactorial systemic inflammatory immune response. Nicotinamide adenine dinucleotide (NAD+) is a co-enzyme involved in cell signaling and energy metabolism. Calcium homeostasis, gene transcription, DNA repair, and cell communication involve NAD+ and its degradation products. There is a growing recognition of the intricate relationship between inflammatory diseases and NAD+ metabolism. In the case of IBD, the maintenance of intestinal homeostasis relies on a delicate balance between NAD+ biosynthesis and consumption. Consequently, therapeutics designed to target the NAD+ pathway are promising for the management of IBD. This review discusses the metabolic and immunoregulatory processes of NAD+ in IBD to examine the molecular biology and pathophysiology of the immune regulation of IBD and to provide evidence and theoretical support for the clinical use of NAD+ in IBD.